El tratamiento de los occitanismos en los diccionarios del español - García Aranda, M. Ángeles (El Colegio de México, 2013)
This paper aims to show the treatment that the voices from the southof France have received in the Spanish lexicography; in this work thehistory of the Occitan words in Spanish are traced in diverse sources:the Tesoros lexicográficos of Spanish language published in the last years,the different editions of Diccionario de la lengua española, by the RealAcademia Española, and in different etymological works.